Advanced parametric louver systems with bi-axis and two-layer designs for an extensive daylighting coverage in a deep-plan office room. (August 2020) - Eltaweel, Ahmad; Su, Yuehong; Lv, Qinghua; Lv, Hui
Highlights: A parametrically-controlled louver system with dual rotation is proposed. The parametric control is based on Grasshopper as a modelling tool. The parametric louver system is either bi-axis or two-layer structure. Additionally, smart windows are used for intensity control. 90% of daylight coverage can be achieved between 300 and 500 lx during the daytime. Abstract: Advanced daylighting systems have become commonly used in modern architecture for a more sustainable environment. The mainstream of recent daylighting studies focuses not only on the quantity but also the quality of daylight delivered to an interior space. The more uniform daylight is distributed in the required illuminance range, the more light stability is achieved, and the longer time is illuminated by daylight, the more electrical lighting energy can be potentially saved. This study proposes an advanced daylighting design based on a parametrically controlled louver with reflective slats to redirect sunlight onto a ceiling, which can then serve as a source of diffuse light to illuminate a room. The design aims to achieve steadier and more uniform daylight distribution during the working hours in a deep-plan office room. The angle of each slat of the louver is parametrically controlled to target a corresponding area on the ceiling. In order to achieve a steadier daylighting, a bi-axis design and a two-layer design with a shifted target are evaluated and compared with a one-axis design. A daylighting analysis of the proposed design is exemplified for a south-oriented 8 m deep office room in a hot arid territory. The daylight analysis was performed using Grasshopper software as a parametric tool to link with Radiance and DAYSIM daylighting analysis. The proposed design shows promising merit that it can provide a relatively steady and distributed daylight coverage for more than 90% of the floor area within the recommended acceptable range 300–500 lx during the working hours.